Infections in Glucose-6-Phosphate Dehydrogenase G6PD-Deficient Patients; Predictors for Infection-Related Mortalities and Treatment Outcomes - Diaa Alrahmany; Ahmed F. Omar; Wael Hafez; Sara Albaloshi; Gehan Harb; Islam M. Ghazi (MDPI AG, 2023)
Disturbances in the count or maturity of blood cells weaken their microbial defensive capacity and render them more susceptible to infections. Glucose-6-phosphate deficient patients are affected by a genetic disease that affects cell integrity with increased liability to infections and death. We aimed to investigate the risk factors for infection mortality in this patient population. We retrospectively examined the records of G6PD adult patients with confirmed infections and collected data related to demographics, infections (pathogens, types, and treatment regimens) in addition to mortality and length of stay outcomes. Data were statistically analyzed using R Programming language to identify contributing factors to mortality and treatment regimens association with outcomes. Records of 202 unique patients over 5 years were included, corresponding to 379 microbiologically and clinically confirmed infections. Patients > 60 years [p = 0.001, OR: 5.6], number of comorbidities 4 (2-5) [p < 0.001, OR: 1.8], patients needed blood transfusion [p = 0.003, OR: 4.3]. Respiratory tract infections [p = 0.037, OR: 2.28], HAIs [p = 0.002, OR: 3.9], polymicrobial infections [p = 0.001, OR: 10.9], and concurrent infection Gram-negative [p < 0.001, OR: 7.1] were significant contributors to 28-day mortality. The history of exposure to many antimicrobial classes contributed significantly to deaths, including β-lactam/β-lactamase [p = 0.002, OR: 2.5], macrolides [p = 0.001, OR: 3.34], and β-lactams [p = 0.012, OR: 2.0]. G6PD patients are a unique population that is more vulnerable to infections. Prompt and appropriate antimicrobial therapy is warranted to combat infections. A strict application of stewardship principles (disinfection, shortening the length of stay, and controlling comorbid conditions) may be beneficial for this population. Finally, awareness of the special needs of this patient group may improve treatment outcomes.